Analysis of the Factors Affecting the Level of Tourist Visits at Puncak Bila Tourism Park - Amir Mahmud (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This study aims to test and analyze the effect of retribution, cost and distance on the number of tourist visits of Puncak Bila tourist park in Sidenreng Rappang Regency. The population in this study was in Sidrap district, and the sampling method used the accindental sampling method, namely random sampling. This study used primary data by providing questionnaires to respodents or peak travelers when. The analysis method in this study uses multiple linear regression analysis with the analysis tool used is SPSS-23. The results showed that in the hypothesis test, the calculated value on all variables was greater than the ttabel, namely Retribution (X1) 6.665; Cost (X2) 3,365; The distance (X3) is 6.696 > 1.98498 with a significant value below 0.05 so that H0 is received which means that levy, cost, and distance are factors that affect the number of tourist visits in Puncak Tourism Park Bila Sidenreng Rappang Regency.